2014
DOI: 10.1097/fpc.0000000000000083
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the folate pathway and transporter polymorphisms on methotrexate treatment outcome in osteosarcoma

Abstract: We have shown that SLCO1B1 polymorphisms influence methotrexate disposition and survival in methotrexate-treated osteosarcoma patients and therefore might serve as pharmacogenetic markers of treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 28 publications
4
42
0
1
Order By: Relevance
“…The rs11045879 and rs4149081 polymorphisms have been associated with methotrexate plasma concentration and toxicity. [19][20][21][22] Neither rs113681054 nor rs4149056 affected efficacy and safety endpoints of patients treated with ticagrelor in the PLATO trial. 7) In agreement with the findings from PLATO trial, we also observed that these two variants exhibited no influence on ticagrelor PD parameters in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The rs11045879 and rs4149081 polymorphisms have been associated with methotrexate plasma concentration and toxicity. [19][20][21][22] Neither rs113681054 nor rs4149056 affected efficacy and safety endpoints of patients treated with ticagrelor in the PLATO trial. 7) In agreement with the findings from PLATO trial, we also observed that these two variants exhibited no influence on ticagrelor PD parameters in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the overall contribution of SLCOB1B variants to explaining interindividual variability in MTX pharmacokinetics is < 15%, and the major genetic contributors are unknown yet. Recently, Goricar et al found that 'low-clearance' SLCOB1B variants were associated with increased MTX disposition (serum levels at 24 h after HDMTX and AUC) and better outcomes in patients with HGOS [6]. As this investigation encompassed only 44 patients, confirmation of the findings in large cohorts are necessary before any firm conclusions can be drawn.…”
mentioning
confidence: 86%
“…Because of its poor diagnosis, a 5-year survival rate of osteosarcoma patients after amputation is only 40 % [4]. Following the development of medical technology, a 5-year survival rate improved significantly and it got up from 50-70 % [5]. However, the mortality ratio of osteosarcoma remains very high because of tumors' rapid migration and proliferation [6,7].…”
Section: Introductionmentioning
confidence: 99%